Preparation and scintillation properties of LGSO:Ce crystals - Sidletskiy, O.Ts.; Bondar, V.G.; Grinyov, B.V.; Kurtsev, D.A.; Baumer, V.N.; Belikov, K.N.; Shtitelman, Z.V.; Tkachenko, S.A.; Zelenskaya, O.V.; Starzhinsky, N.G.; Katrunov, K.A.; Tarasov, V.A. (Functional Materials, 2009)
Lu₂ₓGd₂₋₂ₓSlO₅:Ce single crystals with different Lu/(Lu+Gd) atomic ratio have been obtained by the Czochralski technique. It has been shown that the polymorph transition P2₁/c-C2/c space symmetry at substitution of Gd atoms by Lu takes place at Lu/(Lu + Gd) = 0.1-0.2. The obtained crystals with C2/c symmetry type demonstrate good scintillation characteristics. High Ce³⁺ segregation coefficient together with preferred inclusion of cerium into the seven-fold oxygen - coordinated position provide high light yield and good energy resolution of the crystals. Методом Чохральського вирощено монокристали Lu₂ₓGd₂₋₂ₓSlO₅:Ce з різним атомним співвідношенням Lu/(Lu+Gd). Показано, що поліморфний перехід від просторової симетрії Р2₁/с до С2/с в процесі заміщення атомів гадолінію на лютецій відбувається при співвідношенні Lu/(Lu+Gd)=0.1-0.2. Отримані кристали з типом просторової симетрії С2/с демонструють високі сцинтиляційні характеристики. Високий коефіцієнт входження іонів Се³⁺ у матрицю у поєднанні з переважним входженням церію у семикоординовану позицію киснем обумовлює високий світловий вихід та енергетичну роздільну здатність кристалів. Методом Чохральского выращены монокристаллы Lu₂ₓGd₂₋₂ₓSlO₅:Ce с различным атомным соотношением Lu/(Lu+Gd). Показано, что полиморфный переход при смене пространственной симметрии с Р2₁/с на С2/с в процессе замещения атомов гадолиния на лютеций происходит при соотношении Lu/(Lu+Gd) = 0.1-0.2. Полученные кристаллы с типом пространственной симметрии С2/с демонстрируют высокие сцинтилляционные характеристики. Высокий коэффициент вхождения ионов Се³⁺ в матрицу в совокупности с предпочтительным вхождением церия в семикоординированную позицию по кислороду обусловливает высокий световой выход и энергетическое разрешение кристаллов.